The Moderating Role of Compensation on the Influence of Job Stress and Coworkers on Performance in Medan Adventist Hospital - Peranginangin, Elfrida Br; Siahaan, Marlinda; Sinaga, Judith Tagal Gallena (International Journal of Business, Law, and Education, 2024)
The aim of this research is to analyze and prove the influence of Job Stress and Coworkers on the performance of nurses at Adent Hospital Medan. This research will also prove the moderating effect of compensation on the relationship between Job Stress and co-workers on performance. The population in this study were 150 permanent nurses who worked at the Medan Adventist Hospital. The sampling technique used was Simple Random Sampling, obtaining a sample of 109 respondents. Data analysis techniques use multiple regression with t-test (partial test), F test (simultaneous test) and coefficient of determination test (R2) as well as moderating analysis using residual analysis. The results of this study prove that Job Stress and co-worker variables simultaneously influence nurse performance. Partial testing proves that the Job Stress variable influences nurse performance, as well as the individual Co Workers variable influences nurse performance. Moderation testing using the residual test proves that compensation is able to moderate the relationship between Job Stress and coworkers on nurse performance. The implications of the results of this research are able to prove that the importance of Job Stress management and co-workers in improving nurse performance is strengthened by compensation.